Mouse vascularized adipose spheroids: an organotypic model for thermogenic adipocytes - Davidsen, Laura Ingeborg; Hagberg, Carolina E.; Goitea, Victor; Lundby, Stine Meinild; Larsen, Steen; Ebbesen, Morten Frendø; Stanic, Natasha; Topel, Hande; Kornfeld, Jan-Wilhelm (Frontiers in Endocrinology, 2024)
Adipose tissues, particularly beige and brown adipose tissue, play crucial roles in energy metabolism.Brown adipose tissues' thermogenic capacity and the appearance of beige cells within white adipose tissue have spurred interest in their metabolic impact and therapeutic potential. Brown and beige fat cells, activated by environmental factors like cold exposure or by pharmacology, share metabolic mechanisms that drive non-shivering thermogenesis. Understanding these two cell types requires advanced, yet broadly applicable in vitro models that reflect the complex microenvironment and vasculature of adipose tissues. Here we present mouse vascularized adipose spheroids of the stromal vascular microenvironment from inguinal white adipose tissue, a tissue with 'beiging' capacity in mice and humans. We show that adding a scaffold improves vascular sprouting, enhances spheroid growth, and upregulates adipogenic markers, thus reflecting increased adipocyte maturity.Transcriptional profiling via RNA sequencing revealed distinct metabolic pathways upregulated in our vascularized adipose spheroids, with increased expression of genes involved in glucose metabolism, lipid metabolism, and thermogenesis. Functional assessment demonstrated increased oxygen consumption in vascularized adipose spheroids compared to classical 2D cultures, which was enhanced by β-adrenergic receptor stimulation correlating with elevated β-adrenergic receptor expression. Moreover, stimulation with the naturally occurring adipokine, FGF21, induced Ucp1 mRNA expression in the vascularized adipose spheroids. In conclusion, vascularized inguinal white adipose tissue spheroids provide a physiologically relevant platform to study how the stromal vascular microenvironment shapes adipocyte responses and influence activated thermogenesis in beige adipocytes.